Submicroscopic Changes in the Hepatopancreas of Freshwater Mollusks Infected with Parthenites of Trematodes Echinoparyphium aconiatum (Echinostomida) and Plagiorchis elegans (Plagiorchiida) - Zhytova, O.; Kot , T.; Huralska , S.; Andreieva, O.; Moroz, V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
The study contains the results of the electron microscopic research of the hepatopancreas of Lymnaea stagnalis (Linné, 1758) molluscs infected by the Plagiorchis elegans (Rudolfi, 1802) Braun, 1902 and Echinoparyphium aconiatum Dietz, 1909 trematodes. With a high degree of invasion, fibrous connective tissue growth between lime and liver cells was observed. The number of vacuoles in the cell cytoplasm increased, and the structural organization of the plasma membrane was disrupted. Heterochromatin content decreases in the nucleus, karyorrhexis could occur. The cytoplasm contained single organelles and a large number of electron-dense granules, some cells were destroyed. At a high degree of invasion of L. stagnalis by partenites and cercariae of P. elegans, the nature of the destructive changes in hepatic and lime cells of the hepatopancreas had the same orientation as that of parasites in the mollusks of E. aconiatum trematode. However, the severity of the destructive changes in the hepatopancreas acini of mollusks invaded by the trematode P. elegans was much smaller, as evidenced by the absence of complete destruction of hepatic and lime cells.